Monetary and fiscal policy interactions in a micro-founded model of a monetary union - Roel Beetsma; Henrik Jensen (European Central Bank (ECB), 2002)
So far, the 'new open economy macroeconomics' literature has primarly focused on monetary policy and monetary policy rules, rather than paying attention also to fiscal policy. This is an omission because, especially with the advent of EMU, the burden on fiscal policy as an instrument for macroeconomic stabilization has potentially increased. In this paper, we focus on the interactions between monetary and fiscal policy in a micro-founded model of a monetary union. By extending a two-country, New Keynesian model with public spending, we find that the forward-looking Phillips curves depend on consumption, terms-of-trade and public spending deviations from their respective stochastic natural settings. We study the optimal coordinated monetary and fiscal policy settings for variuos settings. We also consider simple monetary and fiscal policy rules and investigate to what extent these rules can approximate the optimal solution under commitment.
Keywords: E52; E61; E62; E63; F33; 330; monetary policy rules; Policy mix